Fabrikasi dan Karakterisasi Tekan dan Impak Komposit Serat Ijuk/Polimer - Sudarisman Sudarisman (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Randomly oriented chopped sugar palm fiber (SPF)-reinforced epoxy and –reinforced polyester has successfully been fabricated, and their compressive and impact properties have been evaluated. Prior to being used as reinforcement, the SPF was alkali-treated and chopped into 20 mm long. Specimens were cut from a composite plate panel fabricated by means of cold-pressed molding. Compressive and impact tests were carried out according to the AASTM D3410 and ASTM D5410, respectively. It was found that compressive strength and strain-to-failure of SPF/epoxy samples were lower than those of the SFP/polyester samples, but to the contrary, compressive modulus of the SPF/epoxy samples were higher than that of the SPF/polyester samples. Impact toughness of SPF/epoxy specimens was found being higher than that of the SPF/polyester specimens.